Sesamol Alleviates Airway Hyperresponsiveness and Oxidative Stress in Asthmatic Mice - Chian-Jiun Liou; Ya-Ling Chen; Ming-Chin Yu; Kuo-Wei Yeh; Szu-Chuan Shen; Wen-Chung Huang (MDPI AG, 2020)
Sesamol, isolated from sesame seeds (Sesamum indicum), was previously shown to have antioxidative, anti-inflammatory, and anti-tumor effects. Sesamol also inhibited lipopolysaccharide (LPS)-induced pulmonary inflammatory response in rats. However, it remains unclear how sesamol regulates airway inflammation and oxidative stress in asthmatic mice. This study aimed to investigate the efficacy of sesamol on oxidative stress and airway inflammation in asthmatic mice and tracheal epithelial cells. BALB/c mice were sensitized with ovalbumin, and received oral sesamol on days 14 to 27. Furthermore, BEAS-2B human bronchial epithelial cells were treated with sesamol to investigate inflammatory cytokine levels and oxidative responses in vitro. Our results demonstrated that oral sesamol administration significantly suppressed eosinophil infiltration in the lung, airway hyperresponsiveness, and T helper 2 cell-associated (Th2) cytokine expressions in bronchoalveolar lavage fluid and the lungs. Sesamol also significantly increased glutathione expression and reduced malondialdehyde levels in the lungs of asthmatic mice. We also found that sesamol significantly reduced proinflammatory cytokine levels and eotaxin in inflammatory BEAS-2B cells. Moreover, sesamol alleviated reactive oxygen species formation, and suppressed intercellular cell adhesion molecule-1 (ICAM-1) expression, which reduced monocyte cell adherence. We demonstrated that sesamol showed potential as a therapeutic agent for improving asthma.